Obstetric and Perinatal Outcomes in Women ≥40 Years of Age: A Retrospective Study About 421 Cases in Mahdia - Kraiem, Soumaya; Souilem, Leila; Toumi, Dhekra; Bouchahda, Haifa (Gynecology Obstetrics & Reproductive Medicine, 2020)
OBJECTIVES: All this study is aimed to evaluate obstetrical and neonatal outcomes among women age 40 years and older. STUDY DESIGN: Among 9962 women who delivered in Mahdia’s hospital between January 2015 and December 2016, 421 women (4.22%) were 40 years old or older at the time of delivery. Our retrospective study included 421 pregnant women aged more than 40 years and 421 controls aged 18-39, stratified to parity. Data were analyzed using Pearson’s χ22 test. RESULTS: The mean age of the case group was 41.32 years and that for the control group was 31.25 years. Preeclampsia and diabetes were the most common pathologies (p=0.01), the mode of delivery was marked by a high rate of cesarean section. The rate of instrumental extractions was not influenced by age. The rate of neonatal admission and 10-minute Apgar Scores<7 were significantly higher in the older group (p<0.05). The rate of abruption placenta, placenta previa, postpartum hemorrhage, and stillbirth were increased in mothers over 40 years but there was no difference statically. CONCLUSION: Based on findings, maternal age over 40 years is associated with a high rate of obstetrical, medical complications and cesarean section deliveries. Better pregnancy monitoring helps to improve this risky situation.